Kajian Produktivitas Tanaman Pala (Myristica sp.) di Kecamatan Kairatu Barat Kabupaten Seram Bagian Barat - Herman Rehatta; Anna Y. Wattimena; Falmi Tupamahu (JURNAL BUDIDAYA PERTANIAN, 2016)
Nutmeg crop (Myristica sp.) is one of the local specific commodity in Maluku, besides cloves and already well-known as spice crop. However, problems often faced by farmers are the decline of productivity due to factors such as the age of nutmeg tress, the absence of fertilization, bad plant spacing, minimal control of weeds and pests, and lack of availability of seed technology. This research was conducted in the region of western Kairatu Sub-District, Western Seram District, ie. in the villages of Kamal, Nuruwe, and Lohiatala. The purpose if this study was to determine the productivity of nutmeg in the region. The process of collecting data in the field was conducted by using a survey method. The results showed the number of plants in the Nuruwe village were more than in Kamal and Lohiatala villages with various plants spacing.